2010
DOI: 10.1017/s1751731110000406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of culling probability in dairy buffalo using survival models

Abstract: In order to contribute to the genetic breeding programs of buffaloes, this study aimed to determine the influence of environmental effects on the stayability (ST) of dairy female Murrah buffalo in the herd. Data from 1016 buffaloes were used. ST was defined as the ability of the female to remain in the herd for 1, 2, 3, 4, 5 or 6 years after the first calving. Environmental effects were studied by survival analysis, adjusted to the fixed effects of farm, year and season of birth, class of first-lactation milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…Khattab et al (2017) proved that the year of calving had a significant effect on longevity traits. Moreever, the significant effect of the year of first calving on longevity traits reported by (Bashir et al ,2007;Galeazzi et al ,2010 andJakhar et al , 2016), that what agreement with the result reported in this study. And the significant effect of the year on longevity traits may be due to different nutrition and management system at different periods and phenotypic trend (Khattab et al, 2017).…”
Section: Environmental Factorssupporting
confidence: 93%
See 1 more Smart Citation
“…Khattab et al (2017) proved that the year of calving had a significant effect on longevity traits. Moreever, the significant effect of the year of first calving on longevity traits reported by (Bashir et al ,2007;Galeazzi et al ,2010 andJakhar et al , 2016), that what agreement with the result reported in this study. And the significant effect of the year on longevity traits may be due to different nutrition and management system at different periods and phenotypic trend (Khattab et al, 2017).…”
Section: Environmental Factorssupporting
confidence: 93%
“…The longevity traits results of the study were agreement with that recorded by Bashir et al (2007) who found significant effect of herd on longevity traits in Nili-Ravi buffalo. The same results reported by Galeazzi et al (2010) in Murra buffalo in Brazil. In addition to, season of calving effect significantly one productive live and insignificant effect on life time milk yield and herd life (Bashir et al, 2007) that agreement with the results of the present study.…”
Section: Environmental Factorssupporting
confidence: 88%
“…Brazilian buffalo production must increase its efficiency and productivity to attend market demands. Recent studies have shown that buffaloes have significant genetic potential for both production and reproductive traits (Aspilcueta-Borquis et al 2010a,b,c;Galeazzi et al 2010;Seno et al 2010), and Seno et al (2007) found that the high fat and protein percentages in buffalo milk provide high economic returns to Brazilian farmers that produce their own mozzarella cheese. Investments in AI, the adoption of systematic milk-recording programs and genetic evaluations are all tools that can improve the current economic situation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that buffaloes have significant genetic potential for both production and reproductive traits (Aspilcueta‐Borquis et al. 2010a,b,c; Galeazzi et al. 2010; Seno et al.…”
Section: Introductionmentioning
confidence: 99%
“…A high female lifetime production is desirable because it reduces the cost of rearing heifers moreover it allows a greater proportion of culling decisions to depend on production, instead of involuntary culling. Dairy females have been chosen intensively for productivity traits while lifetime production within the herd has decreased (Galeazzi et al 2010 a). In other words, satiability is an important economic trait that is analyzed in some programs of breeding.…”
Section: Introductionmentioning
confidence: 99%